(untitled) (Tigbauan, Iloilo, Philippines, 2004)
This handbook is a user-friendly presentation of technical botanical descriptions - terms are defined in the Glossary - and illustrations of Phillipine mangrove species in Panay Island, Guimaraas and Aurora Province.
Keywords: Cây đước,Mangrove plants; Đảo Panay,Philippines,Panay Island,Philippines